Bank Fraud and Financial Intermediation: A Supply-side Causality Analysis - Daibi W. Dagogo; Tamunonimim A. Ngerebo-a (Athens Journal of Business & Economics, 2018)
This paper investigates supply-side fraud elasticities of financial intermediation. Three rationales that make intermediation inevitable in modern economics were identified as dependent variables: reduction of transaction cost, transformation of risk, and transformation of liquidity. They were represented by operating cost, value-at-risk, and liquidity ratio, respectively. The independent variables stated in monetary value are unauthorized loans, theft & robbery, and fraudulent withdrawal. These variables were preferred after detailed literature review in the area. Three OLS-type multiple regression models were formulated to estimate the values of the dependent variables and the coefficients of the independent variables. Stationarity test, co-integration test, and Granger causality test were conducted for purposes of ensuring reliability of the time series data collected from NDIC, CBN and NBS in respect of the variables listed above. F-test and t-test were conducted to ascertain the statistical significance of the results. The coefficients of the independent variables were then used to evaluate the dependent variables on account of their responsiveness to changes in bank fraud. It was found that financial intermediation is inelastic to bank fraud. It was concluded that as a result of the minute elasticity, financial intermediation cannot be threatened by fraud but incidence of fraud is a signal for intermediaries and regulators to be alive to the responsibilities.